2019
DOI: 10.1001/jamaneurol.2019.1879
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Physical Activity and β-Amyloid With Longitudinal Cognition and Neurodegeneration in Clinically Normal Older Adults

Abstract: In the absence of disease-modifying therapies for Alzheimer disease, there is a critical need to identify modifiable risk factors that may delay the progression of Alzheimer disease. OBJECTIVE To examine whether physical activity moderates the association of β-amyloid (Aβ) burden with longitudinal cognitive decline and neurodegeneration in clinically normal individuals and to examine whether these associations are independent of vascular risk. DESIGN, SETTING, AND PARTICIPANTS This longitudinal observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
104
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 52 publications
15
104
1
5
Order By: Relevance
“…Interestingly, we suggested that more average step counts per day instead of longer walking distance or higher burned calories were associated with better cognition. The finding of importance of step counts is in consistent one recent study demonstrating that physical activity of steps measured by pedometer is associated with amyloid-related cognitive decline and neurodegeneration (Rabin et al, 2019).…”
Section: Average Step Counts Per Day and Cognitionsupporting
confidence: 87%
“…Interestingly, we suggested that more average step counts per day instead of longer walking distance or higher burned calories were associated with better cognition. The finding of importance of step counts is in consistent one recent study demonstrating that physical activity of steps measured by pedometer is associated with amyloid-related cognitive decline and neurodegeneration (Rabin et al, 2019).…”
Section: Average Step Counts Per Day and Cognitionsupporting
confidence: 87%
“…Further, we believe that investigating the maintenance of brain structure and function in the presence of pathologies is an important area of research. For example, exercise may help maintain brain structure and cognition in the face of amyloid [12]. This notion is different from "general" brain maintenance [4] and refers to the maintenance of specific brain processes (see also [5,6]).…”
Section: Lifespan and Cognitive Aging Studiesmentioning
confidence: 99%
“…At a molecular level, exercise produces changes in molecular growth factors such as brainderived neurotrophic factor (BDNF), which plays a crucial role in neuroplasticity and neuroprotection, and increases the production of insulin-like growth factor 1 (IGF-1), involved in both neurogenesis and angiogenesis [43]. Animal and human studies suggest that greater engagement in physical activity may preserve cortical gray matter structure and slow the accumulation of Aβ and tau burden [44].…”
Section: (B) Physical Exercise and Cognitive Functionmentioning
confidence: 99%